2021
DOI: 10.3389/fimmu.2020.590749
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines, Cardiovascular Risk, and Therapeutic Management in Obesity and Psoriatic Arthritis

Abstract: Psoriatic arthritis is a chronic inflammatory disease with skin and joint pathology as the dominant characteristics. Scientific evidence supports its systemic nature and relevant relationship with obesity, metabolic syndrome, and associated conditions. Metabolic syndrome and obesity share common signaling pathways with joint inflammation, reinforcing the idea that adipose tissue is a major contributor to disease development and severity. The adipose tissue is not a mere energy store but also an endocrine organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 108 publications
0
14
0
Order By: Relevance
“… 5 17 18 In short, obesity has been described as a low-grade inflammatory disease, 18 and both obesity and PsA share pathological inflammatory pathways. 5 18 19 Further evidence supporting the association between obesity and a worse PsA clinical outcome is the association of weight loss with higher rate of achieving MDA. 20 Additionally, obesity is a well-known contributor to the metabolic syndrome (MetS), and MetS was similarly associated with lower likelihood of achieving MDA in patients with PsA.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“… 5 17 18 In short, obesity has been described as a low-grade inflammatory disease, 18 and both obesity and PsA share pathological inflammatory pathways. 5 18 19 Further evidence supporting the association between obesity and a worse PsA clinical outcome is the association of weight loss with higher rate of achieving MDA. 20 Additionally, obesity is a well-known contributor to the metabolic syndrome (MetS), and MetS was similarly associated with lower likelihood of achieving MDA in patients with PsA.…”
Section: Introductionmentioning
confidence: 99%
“…Psoriatic arthritis (PsA) is an immune-mediated rheumatic disease,1 with an estimated prevalence of 0.05%–0.42%,2–4 and 5%–41% among patients with psoriasis 3. PsA is a complex and multifactorial disease,5 for which pathological features include musculoskeletal involvement, such as inflammation of the peripheral joints (arthritis), the entheses (enthesitis), the axial skeleton (spondylitis) and the finger and toe digits (dactylitis), as well as extra-articular manifestations involving skin and nails, and potentially other organs 6. Pharmacological treatments include conventional synthetic disease-modifying antirheumatic drugs (csDMARDs) and biologic or targeted synthetic disease-modifying antirheumatic drugs (b/tsDMARDs) 3.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies indicate a positive correlation between Ps and calcium deposition in coronary arteries, as well as endothelial dysfunction caused by chronic inflammation, which is the starting point for atherosclerosis [20]. The combination of these two phenomena -atherosclerotic plaque formation and skin plaques that appear in Ps -is described in the literature as two plaques for one syndrome [21] because they share a similar profile of cytokines secreted by Th1 (tumor necrosis factor α [TNF-α] and interferon γ [IFN-γ]) and Th17 (interleukin 17 and IL-22) lymphocytes [22,23]. A study by Yamazaki [24] indicated that the pro-inflammatory cytokine TNF-α has the greatest impact on atherosclerosis formation.…”
Section: Atherosclerosismentioning
confidence: 99%